2015
DOI: 10.4278/ajhp.140408-quan-134
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Breastfeeding on Early Childhood Obesity: Evidence From the National Survey of Children's Health

Abstract: Purpose. To investigate how breastfeeding initiation and duration affect the likelihood of being overweight and obese in children aged 2 to 5.Design. Cross-sectional data from the 2003 National Survey of Children's Health.Setting. Rural and urban areas of the United States.Subjects. Households where at least one member was between the ages of 2 and 5 (sample size 8207).Measures. Parent-reported body mass index, breastfeeding initiation and duration, covariates (gender, family income and education, ethnicity, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…However, in previous Scandinavian studies of children aged 7 years from Denmark, and aged 15–16 years from Norway, maternal education was found to be more closely associated with obesity than income [ 28 , 29 ]. Studies from the US (all using highest education of either parent) found a stronger association with income than with education [ 30 ], or strong association with both measures of SES [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in previous Scandinavian studies of children aged 7 years from Denmark, and aged 15–16 years from Norway, maternal education was found to be more closely associated with obesity than income [ 28 , 29 ]. Studies from the US (all using highest education of either parent) found a stronger association with income than with education [ 30 ], or strong association with both measures of SES [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of breastfeeding are well-documented for both mothers and children. Breastfed infants are at lower risk for sudden infant death syndrome, 1 more likely to be protected against infections during infancy, 2 less likely to be obese, 3,4 and more likely to have higher IQs. 5 Mothers who breastfeed have a decreased risk of breast and ovarian cancers, better birth spacing, and reduced risk of type 2 diabetes.…”
Section: Introduction and Aimsmentioning
confidence: 99%
“…Moreover, studies in different parts of the world revealed that delayed breastfeeding increases the risk of mental and physical problems at different stages of life (8). Neonatal morbidity and mortality in infants who did not feed breast milk within one hour are increased by threefold when compared to infants who fed breast milk within one hour of birth (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%